PENGARUH PENERAPAN METODE PEMBELAJARAN DEBAT TERHADAP PARTISIPASI BELAJAR SISWA KELAS X SMA NEGERI 7 PEKANBARU PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Cesca Amelta; Hambali; Kingkel Panah Grosman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing the debate learning method on the learning participation of Grade X students at State Senior High School 7 Pekanbaru in the Pancasila Education subject. The low level of students' active participation is caused by the dominance of conventional teacher-centered learning methods that became the main background for conducting this study. The research employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample consist of two classes with a total of 70 students equally divided into an experimental class (X.6, n=35), which used the debate method, and a control class (X.4, n=35), which used conventional methods. Data were collected through questionnaires and observation sheets assessing teacher and student activities. Data analysis was conducted using descriptive and inferential statistical tests in the form of an independent t-test, assisted by IBM SPSS Statistics 25. The results of the hypothesis test in the second meeting showed a significance value (2-tailed) of 0.031 (sig. (2-tailed) < 0.05), leading to the rejection of    and acceptance of   , which indicating a significant difference in learning participation between the two data groups. The effectiveness of the treatment was further supported by an effect size value (Cohen's d) of 0.527, which falls into the medium effect category. Based on these findings, it can be concluded that the debate learning method has a significant positive effect on increasing students’ learning participation in the subject of Pancasila education.